2023
DOI: 10.1007/s00426-023-01869-x
|View full text |Cite
|
Sign up to set email alerts
|

Is happier music groovier? The influence of emotional characteristics of musical chord progressions on groove

Satoshi Kawase

Abstract: Specific rhythmic patterns in music have been reported to induce an urge to move with feelings of pleasure or enjoyment, called “groove.” However, it is unclear how the emotional characteristics of music (e.g., happiness or sadness) affect groove. To address this issue I investigated the effects of the emotional characteristics of music on groove by altering the chord progressions accompanying drum breaks composed by a professional composer while manipulating independent tempo and rhythmic patterns. An online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Groove is defined as the urge to move that is induced by specific rhythmic patterns or music (Madison, 2006;Senn et al, 2016). Similar terms for groove exist worldwide such as "nori" in Japanese (Kawase & Eguchi, 2010;Kawase, 2023), "balanço" in Brazilian (Danielsen et al, 2023), "lüpfig" in Swiss German (Senn et al, 2019), and numerous people share a common groove mechanism (reviewed in Etani et al, 2024). Several acoustic characteristics of music, such as syncopation (Witek et al, 2014;Witek et al, 2017), tempo (Etani et al, 2018), beat clarity (Madison et al, 2011), and bass component (Wesolowski & Hofmann, 2016), induce groove.…”
Section: Characteristics Of Groovementioning
confidence: 99%
See 3 more Smart Citations
“…Groove is defined as the urge to move that is induced by specific rhythmic patterns or music (Madison, 2006;Senn et al, 2016). Similar terms for groove exist worldwide such as "nori" in Japanese (Kawase & Eguchi, 2010;Kawase, 2023), "balanço" in Brazilian (Danielsen et al, 2023), "lüpfig" in Swiss German (Senn et al, 2019), and numerous people share a common groove mechanism (reviewed in Etani et al, 2024). Several acoustic characteristics of music, such as syncopation (Witek et al, 2014;Witek et al, 2017), tempo (Etani et al, 2018), beat clarity (Madison et al, 2011), and bass component (Wesolowski & Hofmann, 2016), induce groove.…”
Section: Characteristics Of Groovementioning
confidence: 99%
“…Indeed, groove can be altered by changing the happiness of chords without changing the rhythm (Kawase, 2023); this suggests that the generation of pleasant feelings induces groove even without changes in rhythmic perceptions. The aforementioned studies have mainly investigated the occurrence of groove in response to external musical stimuli.…”
Section: Pleasurable Feelings Co-occurring With Groovementioning
confidence: 99%
See 2 more Smart Citations
“…Although enjoyable music has not shown an association with groove music (Roberts et al, 2021), happier music has been reported as having higher groove (Kawase, 2023). Since lower tempos are associated with sadness and faster tempos with happiness (Levitin et al, 2018), it is not surprising that fast and happy are both associated with groove.…”
Section: Qualities and Components Of Groove Musicmentioning
confidence: 99%